Entrustment Evidence Used by Expert Gynecologic Surgical Teachers to Determine Residents' Autonomy. (October 2017) - Chen, Xiaodong (Phoenix); Sullivan, Amy M.; Bengtson, Joan M.; Dalrymple, John L.
Abstract : OBJECTIVE: To identify entrustment evidence used by expert gynecologic surgical teachers to determine obstetrics and gynecology residents' level of autonomy in the operating room. METHODS: A qualitative interview study was undertaken from March to November 2016. Four selection criteria were used to define and purposefully sample expert gynecologic surgical teachers across the United States to represent all four geographic regions. All interviews were audio-recorded and transcribed. We applied the Framework Method of content analysis. Transcripts were iteratively analyzed and emergent themes identified. RESULTS: Twenty-seven expert gynecologic surgical teachers from 15 institutions across the United States participated in 30-minute interviews. We identified four domains of entrustment evidence (resident characteristics, medical knowledge, technical performance, and "beyond current surgical case") commonly reported by expert gynecologic surgical teachers to determine residents' autonomy as well as the particular evidence associated with expert gynecologic surgical teachers' determination of resident autonomy at two decision-making points (surgical time-out and taking over certain intraoperative steps) in the operating room. Onsite direct observation and conversation were two common methods used by expert gynecologic surgical teachers to obtain this evidence. CONCLUSION: Entrustment evidence from resident characteristics, medical knowledge, and technical performance domains and from "beyond current surgical case" was commonly used by expert gynecologic surgical teachers to determine residents' autonomy. Our findings provide a potential framework for designing educational interventions that aim to increase residents' readiness for autonomy and entrustment in the operating room. Abstract : Expert gynecologic surgical teachers used entrustment evidence from four domains to determine whether to entrust a resident with autonomy in the operating room.